Population problems of Sri Lanka proceedings of a seminar. (Demographic Training and Research Unit, University of Sri Lanka, Colombo Campus, 1976)
Proceedings of the Seminar on the Population Problems of Sri Lanka in the Seventies, 1975, Colombo, organized by the Demographic Training & Research Unit, University of Sri Lanka, Colombo Campus.